2013
DOI: 10.4018/ijcbpl.2013070101
|View full text |Cite
|
Sign up to set email alerts
|

Violent Video Games and Attitudes Towards Victims of Crime

Abstract: Previous research has indicated that playing violent video games may be associated with an increase in acceptance of violence and positive attitudes towards perpetrators of crime. This study is the first to investigate the relationship between playing violent video games and attitudes towards victims of crime. A total of 206 young people (aged 12-24 years) completed measures of attitudes towards victims and violent video game exposure. The results suggest that exposure to violent video games is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Meta-analytic reviews [26], [27], [28] discovered that playing video games increases children's aggressive cognitions [29], [30]; aggressive emotions [31], aggressive actions [32], and physiological arousal [33]. McLean conducted a study to determine if there was a connection between gaming violence and concern victims and culpable victims, and the results indicated that a direct correlation was evident [34].…”
Section: Negative Aspects Of Playing Gamesmentioning
confidence: 99%
“…Meta-analytic reviews [26], [27], [28] discovered that playing video games increases children's aggressive cognitions [29], [30]; aggressive emotions [31], aggressive actions [32], and physiological arousal [33]. McLean conducted a study to determine if there was a connection between gaming violence and concern victims and culpable victims, and the results indicated that a direct correlation was evident [34].…”
Section: Negative Aspects Of Playing Gamesmentioning
confidence: 99%
“…al., 2010; Ferguson, 2007; Snodgrass, 2016). Current literature also addresses moral panic and the problems with labeling video gaming as an addiction (Billieux et al, 2015; Golub & Lingley, 2008; Kardefelt-Winther et al, 2017; McLean, 2013; Nair, 201; Szablewicz, 20106). This growing culture of video games can be seen trending among the youth and young adults in Arunachal Pradesh, India, also.…”
Section: Introductionmentioning
confidence: 99%